Meningkatkan Kinerja Perusahaan Melalui Strategi Nilai: Peran Market Positioning - Siti Nurjanah (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study aims to determine how value creation, value communication, value delivery can build a market positioning that will have an impact on company performance and create company sustainability. This research uses a qualitative approach. The informants used in this study are creative industry business owners, marketing managers, and consumers. The analysis of this research uses VRIO analysis. The results of this study indicate that value creation. value communication, value delivery will strengthen market position and increase company performance because it will have implications for sustainable competitive advantage. The implication of research can be used by the creative industry as information that can be used for decision making. This research is only limited to the creative industry in Yogyakarta. This research can be developed for other cities value creation, value communication, value delivery, market positioning, performance